Hot iron rods branding, its complications: Still continue in central India - Seema Mahant; C M Reddy; Supriya Mahant; M P Singh (CHRISMED Journal of Health and Research, 2017)
Introduction: The middle of the 20th century has often been described as a golden age of scientific advancement and miraculous medical breakthroughs. In spite of a lot of awareness and many health education programs, still some traditional treatment exists in many places in our country including Central India. In some villages of Madhya Pradesh, many horrifying therapies such as iron rods branding are well known for a few common diseases such as ascites, headache, pneumonia, common cold, or hernia. Bruise marks can be seen on the bodies of a majority of villagers. Main reasons behind such therapy are lack of money for medical treatment, lack of medical facilities, and the unwillingness of medical officers to stay in small villages. Besides this, illiteracy compels them to follow old customs and practices. All these strengthen the faith of villagers in such treatments. It is all due to lack of education and proper awareness. Many female patients come to hospital with complications of iron rods branding suggest that despite being educated, strong cultural beliefs forces people to undergo branding as a treatment of many common diseases in India even in the 21st century. Aims and Objectives: To study the reasons and complications of hot iron branding. Materials and Methods: Sample size was 30. Thirty patients with old, healed (within 1 year), or recent scars of iron branding were included in the study. Patients were evaluated for the sociodemographic details and the information of underlying disease, pattern of lesions, and complications of branding. Results: Hot iron branding is still carrying on as traditional treatment in Central India. It is commonly seen in females of age 20–50 years. It is mostly found in illiterate patients of low socioeconomic status who have chronic disease and chronic pain. Conclusion: Skin branding which still has therapeutic uses in some cultural societies have severe medical complications in Central India.